Structural and Raman properties of silver-doped ZnO nanorod arrays using electrically induced crystallization process. (April 2015) - Tseng, Yi-Wei; Hung, Fei-Yi; Lui, Truan-Sheng; Chang, Shoou-Jinn
Graphical abstract: Highlights: The EIC process is useful to dope metal into the nanostructure. An EIC process significantly improved the crystallinity of nanostructures. The ZnO/Ag structure during EIC process creates the new Raman mode (TH mode). An EIC process could be applied to produce 1D nanostructures of p -type ZnO device. Abstract: The vertically-aligned ZnO:Ag nanorods doped by the electrically induced crystallization (EIC) process at a low temperature, 200 °C, were investigated. The XRD analysis revealed that the EIC process significantly improved the crystallinity and quality of the resulting ZnO nanorods/ZnO thin film. Spectroscopy coupled with XPS confirmed that Ag elements were doped into the ZnO nanorods. The Raman spectrum indicated the strong blue shift of the A1 (TO) and A1 (LO), and there emerged a new Raman mode at 482 cm −1, termed the "TH mode" which is believed to have been created by silver nanoballs appearing on the surface of the silver films. This study demonstrated that EIC is a viable approach to dope the metal elements into nanostructures, and can thus help to produce optical devices with a 1D ZnO p -type structure.